2021
DOI: 10.1002/dc.24841
|View full text |Cite
|
Sign up to set email alerts
|

Direct next‐generation sequencing analysis using endometrial liquid‐based cytology specimens for rapid cancer genomic profiling

Abstract: Background Genomic examination of cytology specimens is often performed on cell blocks or conventional smears rather than on liquid‐based cytology (LBC) specimens. Since LBC specimens preserve high‐quality DNA, cancer genome profiling using next‐generation sequencing (NGS) is also attainable from residual LBC specimens. One of the advantages of using LBC specimens for NGS is that it allows direct extraction of DNA from residual specimens, avoiding a sacrifice of smear slides and minimizing genomic profiling pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“…A recent study reported on the turnaround time of commercially-available plasma tests, reporting a median turnaround time of 9 days [15]. Another report describes rapid NGSbased testing on cytology samples, available within 5 days [16]. To our knowledge, this is the first reported series of cases with comprehensive biomarkers reported in as little as 3 days.…”
Section: Discussionmentioning
confidence: 89%
“…A recent study reported on the turnaround time of commercially-available plasma tests, reporting a median turnaround time of 9 days [15]. Another report describes rapid NGSbased testing on cytology samples, available within 5 days [16]. To our knowledge, this is the first reported series of cases with comprehensive biomarkers reported in as little as 3 days.…”
Section: Discussionmentioning
confidence: 89%
“…14 However, as previously reported, the use of LBC specimens for NGS analysis has a few disadvantages. 28 First, NGS analysis from LBC specimens is performed using residual samples. Although we confirmed the presence of tumor cells in most of the residual LBC specimens and then applied them for DNA extraction, there is a possibility of false-negative materials being applied to NGS.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorometer with a dsDNA BR assay kit (Life Technologies, Grand Island, NY, USA), and DNA quality was confirmed using a QIAseq DNA Quantimize kit (Qiagen). 13,14,16,28…”
Section: Dna Extraction and Quality Assessmentmentioning
confidence: 99%
“…Recent studies have reported the usefulness of LBC samples for NGS analysis. [ 23 24 ] For pancreatic cancer, NGS analysis using LBC specimens was reported to contribute to a possible improvement in the evaluation of pancreatic tumor malignancies and the application of molecular-targeted therapeutic agents. [ 25 ] Preservation of samples is a key step to successful NGS analyses.…”
Section: Discussionmentioning
confidence: 99%